AB0740 The Effect of Pregnancy on Disease Activity Outcomes in Psoriatic Arthritis Patients. (15th July 2016) - Berman, M.; Paran, D.; Wollman, J.; Elkayam, O.
Abstract : Background: Psoriatic arthritis often affects patients at a childbearing age. The relationship between pregnancy and psoriatic arthritis (PsA), in terms of pregnancy outcomes and its effect on disease activity, has not been well studied. Objectives: The aim of this study is to evaluate the effect of pregnancy on disease activity in psoriatic arthritis Methods: A retrospective review of files of female patients followed at the Psoriatic arthritis clinic at the Tel Aviv Medical center was performed and patients with at least 1 pregnancy during follow up and one visit during or soon after pregnancy were included in this descriptive study. A thorough review of the files was performed which included the following data: age, disease duration, pattern of PsA, disease activity before during and after pregnancy, and record of treatment, including intra-articular injections before and during pregnancy. Postpartum period was defined as up to 1 year after pregnancy. PsA as well as psoriasis activity was defined by the treating physician as follow: no disease activity (no active synovitis), mild disease (up to 1 joint involved), moderate to severe disease (more than 2 joints involved). Accordingly, the follow up during and after pregnancy was classified as: improvement, worsening or stable Results: 13 PsA women and 20 pregnancies were identified. 19 resulted in live healthy babies. The mean age at pregnancy was 31.6 years. Table 1 summarizes the status of disease activity before, throughout pregnancy and during the post partum period in the whole group. No significant change in disease activity was noticed throughout pregnancy while a significant proportion of patients flared at post partum Before 12 pregnancies, the patients were treated with TNF α blockers. In 10, the biologic treatment was discontinued close to pregnancy or during the first trimester. In this group, 4 (40%) of patients were classified as mild to severe activity prior to pregnancy. This number increased up to 6 (60%), 7 (70%) and 10 (100%) during the 1st, 2nd trimester and postpartum period respectively. In the 2 patients in whom biologics were not stopped pregnancy, no change in the degree of disease activity was noticed. Interestingly, in the group of non-TNFα treated patients, an improvement in disease activity was observed – the proportion of patients with mild to severe disease activity decreased from 100% close to pregnancy to 71% in the 1st and 2nd trimester and 43% in the 2rd one while an increase to 86% was observed after pregnancy. During 5 pregnancies, corticosteroids (CS) were initiated or the dosage increased - all in pregnancies where TNF α blockers were stopped before pregnancy. Conclusions: Patients with PsA definitively flare after pregnancy. Our results suggest that stopping treatment with TNF α blockers before pregnancy is associated with flare during pregnancy and the post partum period. It seems that in terms of PsA disease activity, it is recommended to continue treatment with TNF α blockers throughout pregnancy Disclosure of Interest: None declared